PROSEDUR VOUCHING AKUN KAS DI KAP DRS. BASRI HARDJOSUMARTO, M.SI, AK & REKAN - Yuliniar Ayu Putri Priaditami; Munari (CV. Adiba Aisha Amira, 2025)
This scientific research examines the role of management assertions in the vouching procedures of cash accounts at KAP Drs. Basri Hardjosumanto, M.Si, AK & Partners, with an emphasis on how management assertions influence the effectiveness and quality of audit procedures for a company. Management assertions, as a process of assessment and evaluation of a client's internal control systems and audit procedures, play a crucial role in ensuring the reliability of cash transaction vouching. This study analyzes the management assertion techniques applied in the vouching procedures, including several assertions used by auditors at KAP Drs. Basri Hardjosumanto, M.Si, AK & Partners, such as existence or occurrence, completeness, accuracy, rights and obligations, and the final assertion, valuation and allocation. The research employs a qualitative approach to gain an in-depth understanding of cash account management for clients through methods involving in-depth interviews to gather detailed information about the processes and practices implemented in companies audited by KAP Drs. Basri Hardjosumanto, M.Si, AK & Partners. The findings indicate that effective management assertions improve the accuracy of vouching by identifying potential errors and areas for improvement in the audit process. This article provides insights into management assertion strategies that can be adopted to enhance vouching procedures in the context of cash account audits at KAP Drs. Basri Hardjosumanto, M.Si, AK & Partners.